Pelatihan Pembelajaran Mendalam untuk Kepala Sekolah Kota Makassar Batch 1 Tahap In 1 - Rahma Ashari Hamzah (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The training program was initiated to enhance the quality of teaching and learning at the school level by introducing the concept of deep learning as a pedagogical approach that honors learners through the principles of consciousness, meaningfulness, and joyful learning. This approach is implemented holistically through the integration of emotional, moral, cognitive, and physical dimensions of learning. The primary objective of the training was to develop participants’ understanding of the deep learning approach so that it can be effectively implemented in their respective educational institutions. A participatory method was employed, involving all participants in the ID class, which consisted of 30 school principals from elementary and junior high schools in Makassar City. The training was conducted from Wednesday to Sunday, 20–24 August 2025, from 08:00 to 16:30 Central Indonesia Time (WITA), at SMKN 6 Makassar, located on Jl. Andi Djemma No. 132, Banta-Bantaeng, Rappocini District, Makassar City. The outcomes of the training included participants’ comprehensive understanding of the deep learning approach, encompassing the development of a growth mindset, the core concepts and framework of deep learning, the alignment of school vision, mission, and learning objectives, leadership in pedagogical practices, leadership in learning partnerships, leadership in creating supportive learning environments, and leadership in digital utilization, as well as the design and implementation of collaborative inquiry. Through these outcomes, participants are expected to be able to apply the deep learning approach effectively within their respective schools.